Designing a Secure Object Oriented Software Using Software Security Life Cycle - Mohammad Obaidullah Bokhari; Mahtab Alam (Institute of Advanced Engineering and Science, 2012)
The security of Object oriented software is well managed by software metrics because they promise accurate, reliable, faster and more efficient ways with proven techniques and standard notations. The Software Security Life Cycle (SSLC) was developed providing a basis to help software Security planning. In this paper, software metrics, which have been proposed for Software Security, are used and applied to programming language. In software industries, the cost of Security of large-scale software has put emphasis on the need to manage the in earlier phases and is statistically estimate the security of large software system and to identify error prone modules.